Biomaterials in Regenerative Medicine - Dobrzański, Leszek A. (IntechOpen, 2018)
The book Biomaterials in Regenerative Medicine is addressed to the engineers and mainly medical practitioners as well as scientists and PhD degree students. The book indicates the progress in research and in the implementation of the ever-new biomaterials for the application of the advanced types of prosthesis, implants, scaffolds and implant-scaffolds including personalised ones. The book presents a theoretical approach to the synergy of technical, biological and medical sciences concerning materials and technologies used for medical and dental implantable devices and on metallic biomaterials. The essential contents of the book are 16 case studies provided in each of the chapters, comprehensively describing the authors' accomplishments of numerous teams from different countries across the world in advanced research areas relating to the biomaterials applied in regenerative medicine and dentistry. The detailed information collected in the book, mainly deriving from own and original research and R&D works pursued by the authors, will be beneficial for the readers to develop their knowledge and harmonise specific information concerning these topics.